Acute Aerobic Exercise Increases Brain-Derived Neurotrophic Factor Levels in Elderly with Alzheimer's Disease - Melo Coelho, Flavia Gomes de [UNESP]; Vital, Thays Martins [UNESP]; Stein, Angelica Miki [UNESP]; Arantes, Franciel Jose [UNESP]; Rueda, Andre Veloso; Camarini, Rosana; Teodorov, Elizabeth; Santos-Galduroz, Ruth Ferreira [UNESP] (IOS Press, 2014)
Studies indicate the involvement of brain-derived neurotrophic factor (BDNF) in the pathogenesis of Alzheimer's disease (AD). Decreased BDNF levels may constitute a lack of trophic support and contribute to cognitive impairment in AD. The benefits of acute and chronic physical exercise on BDNF levels are well-documented in humans, however, exercise effects on BDNF levels have not been analyzed in older adults with AD. The aim of this study was to investigate the effects of acute aerobic exercise on BDNF levels in older adults with AD and to verify associations among BDNF levels, aerobic fitness, and level of physical activity. Using a controlled design, twenty-one patients with AD (76.3 +/- 6.2 years) and eighteen healthy older adults (74.6 +/- 4.7 years) completed an acute aerobic exercise. The outcomes included measures of BDNF plasma levels, aerobic fitness (treadmill grade, time to exhaustion, VO2, and maximal lactate) and level of physical activity (Baecke Questionnaire Modified for the Elderly). The independent t-test shows differences between groups with respect to the BDNF plasma levels at baseline (p = 0.04; t = 4.53; df = 37). In two-way ANOVA, a significant effect of time was found (p = 0.001; F = 13.63; df = 37), the aerobic exercise significantly increased BDNF plasma levels in AD patients and healthy controls. A significant correlation (p = 0.04; r = 0.33) was found between BDNF levels and the level of physical activity. The results of our study suggest that aerobic exercise increases BDNF plasma levels in patients with AD and healthy controls. In addition to that, BDNF levels had association with level of physical activity.
Keywords: Aerobic exercise; Alzheimer's disease; brain-derived neurotrophic factor; neurotrophic factors; physical activity